Effect of Bis (2-Aminoethyl) Adipamide/Adipic Acid Segment on Polyamide 6: Crystallization Kinetics Study - Yu-Hao Chen (Polymers, 2020)
The crystallization behavior of novel polyamide 6 (PA6) copolyamides with different amounts of bis (2-aminoethyl) adipamide/adipic acid (BAEA/AA) segment was investigated. The wide-angle X-ray diffraction (WAXD) results showed that as the amount of BAEA/AA segment increased to 10 mole%, the crystalline forms of all PA6 copolyamide were transferred from the stable α-form to the unstable γ-form because of the complex polymer structure. According to studies of crystallization kinetics, the Avrami exponent (n) values for all copolyamide samples ranged from 1.43 to 3.67 under isothermal conditions, implying that the crystallization is involved in the two- to three-dimensional growth at a high temperature of isothermal condition. The copolyamides provided a slower crystallization rate and higher crystallization activation energy (ΔEa) than neat PA6. Polyamide containing 10 mole% of BEAE/AA content exhibited a unique crystallization behavior in the coexistence of the α and γ forms. These results deepen our understanding of the relationship between BAEA/AA content, crystal structure, and its crystallization behavior in low-melting PA6, and they make these types of copolyamides useful for their practical application.